56 Impact of Electronically-Controlled Cooling Pads on Physiological Signs of Heat Stress in Early Lactation Sows. (30th November 2020) - Whitmore, Flannery J; Schinckel, Allan P; Stwalley, Robert; Field, Tyler; Burgett, Morgan; Garcia, Ricardo M; Johnson, Jay S
Abstract: The study objective was to evaluate the impact of electronically controlled cooling pads on physiological measurements of heat stress during early lactation. Twelve sows (d 3 to 11 of lactation) were provided with a specially designed cooling pad. Sows randomly received no cooling (CONTROL, n=6) or pads set to flush 2L cool water every 30s when aluminum plate reached 29.5°C (TREAT, n=6). Respiration rates (RR), rectal temperatures (RT) and skin temperatures (ST, 15 cm posterior to the ear) were recorded daily (0700 and 1500 h) for seven days of early lactation. Feed intake (DFI) was measured daily at 0700 h. RR, RT, and ST were fitted to a model that included the effects of day, time, parity, cooling pad treatment, and interactions. DFI was fitted to the same model, excluding time of day. For RR: treatment, day, time, treatment by day, treatment by time, and day by time interactions were significant (P< 0.0004, CONTROL=49, TREAT= 30). Pad treatment had greater impact on RR during the first two days of the trial when the temperature was greater (32°C maximum CONTROL mean=66 vs. TREAT mean=30) than the following five days: 42, and 30 respectively). There was greater treatment impact on RR at 1500 versus 0700 h (0700 h: CONTROL= 35, TREAT= 25; 1500 h: CONTROL= 61, TREAT= 36). For RT: treatment, day, time, parity and interaction of day by time were significant (P< 0.01, CONTROL= 37, treat= 35.). For ST: treatment, day, time, parity and the interactions of time by parity, treatment by time, and day by time were significant (P< 0.0006, mean CONTROL=36.5, TREAT= 35.1). For DFI: day and the interaction of day by treatment were significant. The difference in feed intake between treatments increased as day increased. The use of electronically controlled cooling pads reduced measures of heat stress in early lactating sows.